2009
DOI: 10.1152/ajpregu.90848.2008
|View full text |Cite
|
Sign up to set email alerts
|

Prior heavy exercise elevates pyruvate dehydrogenase activity and muscle oxygenation and speeds O2uptake kinetics during moderate exercise in older adults

Abstract: (V O2p) kinetics during the transition to moderate-intensity exercise is slowed in older compared with younger adults; however, this response is faster following a prior bout of heavy-intensity exercise. We have examined V O2p kinetics, pyruvate dehydrogenase (PDH) activation, muscle metabolite contents, and muscle deoxygenation in older adults [n ϭ 6; 70 Ϯ 5 (67-74) yr] during moderate-intensity exercise (Mod 1) and during moderate-intensity exercise preceded by heavy-intensity warm-up exercise (Mod2). The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
34
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 57 publications
2
34
2
Order By: Relevance
“…The correlation between resting muscle oxygenation and V O 2 kinetics in the present study (Fig. 4), however, suggests that the flux control for V O 2 kinetics may be more sensitive to O 2 delivery in CHF patients than in the healthy population (20,21).…”
Section: Discussioncontrasting
confidence: 63%
See 4 more Smart Citations
“…The correlation between resting muscle oxygenation and V O 2 kinetics in the present study (Fig. 4), however, suggests that the flux control for V O 2 kinetics may be more sensitive to O 2 delivery in CHF patients than in the healthy population (20,21).…”
Section: Discussioncontrasting
confidence: 63%
“…In healthy young and elderly individuals, prior exercise has had varied success in speeding V O 2 kinetics. Some studies have shown a benefit, but only when the warm-up exercise exceeded the LT (11,20,21). Only one previous study (in heart transplant recipients) has reported a speeding of V O 2 kinetics following prior moderate exercise (38).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations